1988
DOI: 10.1111/j.1471-4159.1988.tb01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Amino Acids by Brain Micro vessels Isolated from Rats with Experimental Chronic Renal Failure

Abstract: The neurological disorders seen in patients with chronic renal failure and liver cirrhosis are analogous. Previous in vivo studies have shown that the impaired blood-brain amino acid transport seen in rats with chronic renal failure is similar to that of rats with portocaval anastomosis. To elucidate whether a comparable underlying pathogenic mechanism plays a role in both pathological conditions, blood and brain amino acid levels together with amino acid transport by isolated brain microvessels have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The observations that both ammonia treatment in vitro and hepatic encephalopathy in vivo potentiated the TRY-stimulated Gln release is consistent with the enhanced TRY and other neutral amino acids uptake into capillaries pretreated with Gln (Cangiano et al, 1983) or ammonia (Cardelli-Cangiano et al, 1984), or derived from rats subjected to different hyperammonemic conditions (Cardelli-Cangiano et al, 1981;Cangiano et al, 1988). Cardelli-Cangiano et al (1984) suggested an indirect mechanism of stimulation by ammonia, i.e., via the synthesis of excess Gln.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The observations that both ammonia treatment in vitro and hepatic encephalopathy in vivo potentiated the TRY-stimulated Gln release is consistent with the enhanced TRY and other neutral amino acids uptake into capillaries pretreated with Gln (Cangiano et al, 1983) or ammonia (Cardelli-Cangiano et al, 1984), or derived from rats subjected to different hyperammonemic conditions (Cardelli-Cangiano et al, 1981;Cangiano et al, 1988). Cardelli-Cangiano et al (1984) suggested an indirect mechanism of stimulation by ammonia, i.e., via the synthesis of excess Gln.…”
Section: Discussionsupporting
confidence: 63%
“…Cardelli-Cangiano et al (1984) suggested an indirect mechanism of stimulation by ammonia, i.e., via the synthesis of excess Gln. However, these authors preincubated the capillaries with ammonia 20 min prior to uptake measurements, which favored de novo synthesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the plasma of uremic patients, elevated concentrations of PHE were found [22], which may be attributed to an abolished renal uptake of PHE in the uremic state [23] and a defective hydroxylation of PHE resulting from partial inhibition of the enzyme phenylalanine hydroxylase [24,25]. In addition, a significantly greater uptake of PHE was shown in brain microvessels isolated from rats with chronic uremia [26]. In keeping with these findings, the brain tissue of the deceased with advanced renal disease in our study exhibited an elevated concentration of PHE.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding that rat plasma l-arginine concentrations are not altered following partial nephrectomy is consistent with previous reports. 15,33,34 In a rat experimental model of renal mass reduction, hypertrophy of the proximal tubule in the remnant nephrons resulted in an increase in l-arginine synthesis per nephron. 11 It is also possible that extrarenal tissues maintain normal plasma levels of l-arginine.…”
Section: Discussionmentioning
confidence: 99%